Hope and history : a memoir of tumultuous times - Vanden Heuvel, William J. (William Jacobus), 1930- (Cornell University Press, 2019)
"The uniquely American story of Ambassador William vanden Heuvel, who rose from modest immigrant beginnings to embrace an extraordinary life in politics and public service alongside Roosevelts, Kennedys, and some of the most important American political figures of the 20th century"--